P‐122: High Quantum Yield Green and Red CdSe/CdS Dot‐in‐Rods and Their Electroluminescent Light Emitting Diodes. Issue 1 (29th May 2019) - Zhou, Ziming; Liu, Haochen; Hao, Junjie; Wang, Kai; Teo, Kie Leong; Sun, Xiao Wei
Abstract : We successfully synthesized CdSe/CdS dot‐in‐rods (DiRs) with a high quantum yield (QY, 70% and 65% for green and red). And these DiRs were further utilized to fabricate DiRs electroluminescent (EL) light emitting diodes (LEDs), as the first‐time report for green LED and record‐high performance for red LED. This kind of DiRs can be utilized for high efficiency and color gamut display technologies.